Cerebral Mycobacterium avium abscesses: Late immune reconstitution syndrome in an HIV-1-infected patient receiving highly active antiretroviral therapy - Claude Fortin; Danielle Rouleau (Canadian Journal of Infectious Diseases and Medical Microbiology)
A patient who developed an atypical manifestation of Mycobacterium avium complex (MAC) infection almost two years after starting effective highly active antiretroviral therapy is described. The recurrence, manifested as brain abscesses in the central nervous system, was an uncommon form of MAC disease usually reported postmortem. An increased CD4 cell count, localized and suppurative infection, and the absence of systemic evidence of infection were consistent with a late immune reconstitution syndrome. The present case report adds to the understanding of MAC disease in HIV-infected patients.